Dermatomycosis among Elementary School Children in Jatinangor West Java - Isni Maulina Sukmara; Risa Miliawati; Hadyana Sukandar (Faculty of Medicine Universitas Padjadjaran, 2015)
Background: Dermatomycosis often occurs in tropical countries. Many studies from tropical countries have reported high prevalence of dermatomycosis among elementary school children. Despite being a tropical country, prevalence of dermatomycosis among elementary school children in Indonesia is still unknown.The objective of this study was to determine the prevalence and characteristics of dermatomycosis among elementary school children in Jatinangor, Sumedang, West Java in September–November 2012.Methods: This study used a cross-sectional descriptive survey method. The 328 children from five elementary schools in Jatinangor were included in the study using multistage sampling technique. Medical history and physical examination was performed to all subjects. Subjects who had skin lesion suspected fordermatomycosis were examined with direct microscopic examination using 10% solutions of potassium hydroxide (KOH). Data were presented as frequent analysis distribution using Statistical Package for Social Sciences (SPSS) version 17.0.Results: Of 328 children (174 males, 154 females; aged 5–14 years), 35 (10.6%) had lesions suggestive of dermatomycosis but only 5 children (1.5%) were positive for dermatomycosis. Males are more prevalent females, patients were in ≥10 years age group. Four cases were Pityriasis versicolor, while one was diagnosed with tinea facialis.Conclusions: Dermatomycosis among elementary school children in Jatinangor had a low prevalence, with only 4 cases of Pityriasis versicolor and one tinea facialis case. [AMJ.2015;2(1):268–75]